2021
DOI: 10.2174/0929867327666200515101228
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: A Dietary Phytochemical for Targeting the Phenotype and Function of Dendritic Cells

Abstract: : Dendritic cells (DCs) are the most powerful antigen-presenting cells which link the innate and adaptive immune responses. Depending on the context DCs initiate the immune responses or contribute to immune tolerance. Any disturbance in their phenotypes and functions may initiate inflammatory or autoimmune diseases. Hence, dysregulated DCs are the most attractive pharmacological target for the development of new therapies aiming at reducing their immunogenicity and at enhancing their tolerogenicity. Curcumin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…Although, the immune-modulatory actions of Curcumin have been shown in a wide range of in ammatory and autoimmune diseases such as arthritis, colitis and hepatitis, its immunomodulatory capacity in the TME has emerged relatively recently. Research has shown that Curcumin not only enhances tumor antigen-speci c T cells via reversal of tumor-induced immunosuppression but also enhances cytotoxic T cells by acting directly on immune cell dysfunction, which is one of the major mechanisms of tumor escape from immune surveillance via the signal transducer and activator of transcription 3 and nuclear factor kappa B (NF-kB) signaling pathways [23,43,44]. Lim et al [45]showed inhibition of in ammation-mediated PD-L1 expression by Curcumin, and Liao et al [46] showed decreased PD-L1 expression following immunosuppression in cell populations, such as Tregs and myeloid-derived suppressor cells, in a murine oral cancer model after Curcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the immune-modulatory actions of Curcumin have been shown in a wide range of in ammatory and autoimmune diseases such as arthritis, colitis and hepatitis, its immunomodulatory capacity in the TME has emerged relatively recently. Research has shown that Curcumin not only enhances tumor antigen-speci c T cells via reversal of tumor-induced immunosuppression but also enhances cytotoxic T cells by acting directly on immune cell dysfunction, which is one of the major mechanisms of tumor escape from immune surveillance via the signal transducer and activator of transcription 3 and nuclear factor kappa B (NF-kB) signaling pathways [23,43,44]. Lim et al [45]showed inhibition of in ammation-mediated PD-L1 expression by Curcumin, and Liao et al [46] showed decreased PD-L1 expression following immunosuppression in cell populations, such as Tregs and myeloid-derived suppressor cells, in a murine oral cancer model after Curcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The natural spice curcumin has received recent attention in treating diseases involving perturbations of the immune system and inflammation responses, such as COVID-19 [12][13][14][15]. Curcumin and other curcuminoids are the main bioactive ingredients of turmeric (Curcuma longa).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intervening in the regulatory network of CCR7 also shows great prospect for inflammatory disease remission. Cyclosporin A, triptolide, and curcumin were found to inhibit LPS-triggered upregulation of COX-2, PGE2, NF-κB, and AP-1 along with subsequent CCR7 expression, thus impairing the chemotaxis of DCs to CCL19/21 and motivating tolerance in diseases (Chen et al, 2004;Liu et al, 2007;Rahimi et al, 2021). Semaphorin 3E may regulate IRF4 to alter CCR7 levels and benefit allergic airway hyperresponsiveness (Movassagh et al, 2021).…”
Section: Immunotherapy Targeting Ccr7 Directlymentioning
confidence: 99%